NILAI-NILAI PENDIDIKAN AKHLAK DALAM KITAB AL-BARZANJI - Hayaturrohman Hayaturrohman; Arif Rahman; Rayhand Eljinand (Mozaic : Islam Nusantara, 2020)
This research is motivated by the history of Islamic culture in the territory of Indonesia which is growing up to the present, both among rural and urban communities. One of them is the phenomenon of the reading of the book al barzanji with a variety of ways and methods. Exploring meaning in depth is also important considering that not a few people who read it, but he does not know what the meaning and meaning contained in the Book of al- Barzanji. This research is based on the idea that moral education is one of the important things that must be considered. Theoretically moral education references can come from various sources, one of which is a written source, in this case the Book of Al-Barzanji that explains the character of the Prophet Muhammad. The research method used is the content analysis method because this research is a study of the text contained in the book of al- Barzanji and through a qualitative analysis approach. This research emphasizes the power of data analysis (content analysis) on data sources obtained from books, writings or so-called literature studies and by relying on existing theories to be interpreted broadly and deeply. The data collection technique used is Literature Study, by collecting books / documents related to research. The primary source is Al-Barzanji by Shaykh Ja'far al-Barzanji. Based on the results of the study, obtained two things, the first is the value of moral education contained in the book Al-Barzanji includes six core values, namely: Al-Sidqu's value (honest); the value of al-Ulfah (merciful); the value of al-fAfwu (forgiving); Anisatun rating (friendly) ; the value of al-Khairu (kindness);Simple and Juhud values (have a work ethic).